Thermal and entropy performance of nano enhanced phase change materials-water nanofluids in a chamber with distributed heating - Rajesh, Vemula; Öztop, Hakan Fehmi (Aip Publishing, 2025)
This study presents a detailed numerical investigation of nonlinear thermo-fluid interactions and phase change dynamics in a Nano Enhanced Phase Change Material (NEPCM)-water nanofluid-filled chamber subjected to distributed heating, focusing on how key governing parameters influence heat transfer and entropy generation. Using the Galerkin finite element method, the coupled effects of Rayleigh number (Ra), fusion temperature (theta(f)), Stefan number (Ste), and NEPCM volume fraction (phi) are analyzed. Results show a non-monotonic influence of theta(f), with theta(f)= 0.3 yielding the highest Nusselt number and theta(f)= 0.5 minimizing entropy generation. Heat capacity ratio (Cr) contours highlight efficient thermal storage near theta(f)= 0.5. Low Ste (Ste = 0.1) enhances latent heat absorption, strengthening convection and reducing thermodynamic losses. Increasing phi improves heat transfer with only a modest rise in entropy generation. These findings highlight optimal performance conditions and demonstrate that precise tuning of fusion temperature (theta(f)) and Stefan number (Ste) can markedly improve the thermal efficiency and storage capability of NEPCM-enhanced convective systems.
Keywords: Energy Storage; Convective Flow; Generation; Cavity